Road network analyses elucidate hidden road flooding impacts under accelerating sea level rise - Mitchell, Molly; Hendricks, Jessica; Schatt, Daniel (Frontiers in Environmental Science, 2023)
Introduction: As sea level rises and coastal communities simultaneously grow, road flooding has the potential to significantly disrupt travel along road networks and make houses, businesses, and critical facilities difficult to reach. The impacts of tidal and storm surge flooding on roadways present challenging social and economic considerations for all coastal jurisdictions. Maintenance, public and private accessibility, evacuation routes, emergency services are just a few of the common themes local governments are beginning to address for low-lying roadways currently known to flood. Continuation of these services allows a community to thrive, to maintain or increase its tax base, and to ensure the safety and well-being of its citizenry. Methods: A traditional approach to analyzing road flood overlays flooding areas on roadways and focuses only on impacts within the actual zone of inundation. However, road flooding can also cut-off access to non-flooded roads and properties, closing the transportation corridor into or out of their downstream dwelling/service areas and other areas that may be impacted. In this study, we examined changing road inaccessibility under accelerating sea level rise for urban and rural localities. Results: Inaccessibility of roads and properties increased nearly twice as much as would be suggested by the length of flooded roads. Overall vulnerability of a locality was primarily dependent on its elevation; however, the redundancy of the road network appears to affect the rate at which properties became inaccessible. Areas with complex and redundant road networks-maintained access to coastal properties longer, suggesting increased resilience in the near term. Discussion: Road inaccessibility will impact property values and emergency response times but understanding the connection between flooding areas and inaccessible properties allows prioritization of road upgrades, improving overall coastal resilience.